Fine Arts Palace (Pacific Novelty Co.)
On verso: The Palace of Fine Arts.Erected as part of the Panama-Pacific International Exposition, was designed by R. Maybeck, and called forth more eulogiums than any other individual building in the Exposition. The building is the arc of a circle form, and its outer circumference measures 1100 feet. The Rotunda, surmounted by a dome 162 feet high and 116 feet in diameter, stands within a small lake, which mirrors its classic outlines. In response to an unanimous public demand this splendid building was retained permanently by the city.